Lives and works in the arts : from the Renaissance to the 20th century. - M.E. Sharpe (Armonk : Sharpe Reference, 2002)
Surveys the lives and works of European and American writers, artists, and composers from the Renaissance into the twentieth century.
Includes bibliographical references and index.
Keywords: Artists; Arts bibliography; Arts,modern; Arts, Modern-history; Artists; Authors; Composers